Return to football training and competition after lockdown caused by the COVID-19 pandemic: medical recommendations - Bisciotti, G. N.; Eirale, C.; Corsini, A.; Baudot, C.; Saillant, G.; Chalabi, H. (Biology of Sport, 2020)
The lockdown caused by the COVID-19 pandemic represents a great unknown regarding the physiological changes induced in elite football players. Although it will differ from country to country, the return to sport for professional football players will follow a forced lockdown never experienced and longer than the normal annual season break. Moreover, in addition to an obvious decrease in performance, the lockdown will possibly lead to an increase of the injury risk. In fact, preseason is always a period with a specific football injury epidemiology, with an increase in the incidence and prevalence of overuse injuries. Therefore, it seems appropriate to recommend that specific training and injury prevention programmes be developed, with careful load monitoring. Training sessions should include specific aerobic, resistance, speed and flexibility training programmes. The aerobic, resistance and speed training should respect some specific phases based on the progressiveness of the training load and the consequent physiological adaptation response. These different phases, based on the current evidence found in the literature, are described in their practical details. Moreover, injury prevention exercises should be incorporated, especially focusing on overuse injuries such as tendon and muscle lesions. The aim of this paper is to provide practical recommendations for the preparation of training sessions for professional footballers returning to sport after the lockdown.